نظريات التحديث الأوروبية وانعكاساتها في الفكر الاقتصادي العربي المعاصر (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2016)
أنجز الغرب مشروعة الحضاري في إطار علاقة سليمة بين الفكر والواقع, منجزاً إبرام عملية قطع و قطيعة ابستمولوجية مع الفكر اللاهوتي والميتافيزيقي مستبدلاً ذلك بفكري وضعي ومنهج تجريبي عقلي قائم على الملاحظة والتجربة, من هنا انطلق الغرب بانياً نهضته التي انطلقت في تأثيرها نحو الخارج بعد أن تكللت تجربتها بالداخل نجاحاً, تأثرت مجتمعاتنا وأنساقنا المجتمعية بالتحديث الأوروبي, وبصور متباينة, تباين منسوب التناقضات التي تعيشها هذه المجتمعات, فالنسق الاقتصادي الأكثر إفصاحاً عن نفسه من بقية الأنساق, في التعبير عن نفسه, وتوصيف علاقاته مع بيئته والبيئات الخارجية, ومستويات الفشل والنجاح, تأثر النسق الاقتصادي بالتحديث الغربي ولكن لم يتجاوز التأثر إلى التأثر إلى الفعل والفاعلية, فالاستقلالية وصولاً إلى بناء منظومة اجتماعية اقتصادية تحاكي مبدأ إحداث القطيعة مع كل ما من شأنه إعاقة إقامة عقد اجتماعي من نوع جديد يخرج هذه المجتمعات من حالة التردي غلى حالة التعافي و إنجاز مشروعها الحضاري. The West has achieved its civilization project within the homework of a second relationship between thought and reality. It has achieved an epistemological process with theological and metaphysical thought replacing it with secular thought and a mental empirical approach based on observation and experiment. It is from their point that the West started building its renaissance where influence targeted the external world after its experience was so successful at the local level. Our societies and social levels have been influenced by the European modernization process in various ways. The variety of influence varied in accordance with the contradictions there societies are experiencing. The economic level which is the most self-expressing and which outliner its relations with its environment and external environments as well as with levels of failure and success has been influenced by the Western modernization process. However, it has not gone beyond the point of influenced to the point of being influencing or to the point of action, efficiency and independence or even to the point of developing a social and economic system that could imitate the estrangement with everything that may obstruct the establishment of a new kind of social contract that would move their societies from a deteriorating situation to a situation of recovery and achieve a civilization project.